THE WORDS RELATED TO UZBEK FAMILIES: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
In this article it has been given information about the words which are related to family. Uzbek families’ respect to family members as well as politeness can be the best example among the nations. So these words and their common types are compared with different nations.